"A Dream to Go Abroad": Undocumented Student Participation in Education Abroad. Issue 4 (7th August 2020) - Madden, Meggan Lee; Butler, Paige E.; Smith, Nickie
Abstract : This phenomenological study examined the lived experiences of eight undocumented students who successfully studied abroad between 2012 and 2016. In-depth interviews of students at a public research university in California articulate the determination, resourcefulness, and unspoken fears that undocumented students carried with them throughout the higher education experience. This study identifies the consequences of policies on the student experience and provides implications for student affairs professionals who work in and outside the United States.